Moose - Ballard, Jack (Jack Clayton) (Falcon field guide., 2014)
This book contains all the information you need to know to become familiar with these fascinating animals. Accompanied by numerous full-color photos of moose in their natural habitat, this handy field guide makes an excellent take-home souvenir and reference for anybody interested in moose.